PENGARUH DIVERSIFIKASI PRODUK YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DENGAN MEDIASI KEPERCAYAAN KONSUMEN PADA TOKO UD SUBUR DI KABUPATEN BONDOWOSO - Septiawati, Rizky Aulia; Karnadi, Karnadi; Wiryaningtyas, Dwi Perwitasari (Fakultas Ekonomi dan Bisnis, 2022)
Product diversification is an effort made by the company to diversify products or services by creating new products or services to suit the taste and needs of consumers so as to increase sales. The purpose of this stufy was to analyze and examine the effect of product diversification that influences purchasing decisions by mediating consumer trust at the UD Subur store in Bondowoso regency. The pupolation in this study were UD Subur consumers, the sampling technique was determined by probability sampling. Analyze of data and hypotheses in this study used the Structural Equation- Partial Least Square (PLS-SEM) model. Hypotheses test result directly using the Smart PLS 3.0 application. Show that product diversification has a significant positive effect on consumers confidence, product diversification has significant positive effect on purchasing decisions. The result of the indirect effect test show that the product diversification variable on purchasing decisions through consumer trust has a significant positive effect.